Analisis Hukum Islam terhadap Wakaf uang sebagai Instrumen Keuangan Syariah di Indonesia - Alfawwaz, Qathrina Qanitatin Nadhirah; Hilmi, M. Faiq Mufadhol; Wigati, Sri (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The practice of cash waqf in Indonesia has grown rapidly in recent decades as one of the Islamic financial instruments that is increasingly recognized and accepted by the Muslim community. The practice of cash waqf in Indonesia is supported by the fatwa of the Indonesian Ulema Council (MUI) and comprehensively regulated in Law No. 41/2004 on Waqf. The government also plays an active role through the establishment of the Indonesian Waqf Board (BWI) as an independent institution authorized to promote and develop waqf, including cash waqf. This research aims to analyze the validity and suitability of cash waqf practices in Indonesia based on Islamic law. The research method used is qualitative analysis with a literature study approach. The results show that the practice of cash waqf in Indonesia can be qiyaskan (analogized) with other movable object waqf which is justified in Islamic law